Barcode enabled m-commerce: strategic implications and business models. (11th January 2006) - Scornavacca Jr., Eusebio; Barnes, Stuart J.
This paper provides background on the use of barcodes for the provision of mobile commerce (m-commerce) services. It presents three cases where this technology has been used – in Japan, New Zealand and the UK. Subsequently, these are used as the basis for a discussion and analysis of the key business models and strategic implications for particular markets. The paper concludes with predictions for the market and directions for future research.